2019
DOI: 10.1111/exd.13828
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocapsule of α‐lipoic acid reveals pigmentation improvement: α‐Lipoic acid stimulates the proliferation and differentiation of keratinocyte in murine skin by topical application

Abstract: α‐Lipoic acid is amphipathic with low molecular sulphur‐containing fatty acid and has strong antioxidant effects. It has been used at the purposes of anti‐ageing, treatment of diabetic neuropathy, and supplement as antioxidant. Though α‐lipoic acid is normally administered in oral or injection, it has not been used in a topical use via skin because of its bad penetration. We developed the novel nanocapsule of α‐lipoic acid, named α‐lipoactive (nLA), to improve skin permeability. The nLA is constructed as micel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
9
0
2
Order By: Relevance
“…Developed novel nanocapsule of ALA, named α-Lipoactive (nLA), to improve skin permeability. In in vivo experiments, it was found that nLA is very effective for improving UV-induced pigmentation and epidermal thickening [151]. Demonstrated application of topical 30% poloxamer gel loaded with ALA cubosomes.…”
Section: G α-Lipoic Acidmentioning
confidence: 99%
“…Developed novel nanocapsule of ALA, named α-Lipoactive (nLA), to improve skin permeability. In in vivo experiments, it was found that nLA is very effective for improving UV-induced pigmentation and epidermal thickening [151]. Demonstrated application of topical 30% poloxamer gel loaded with ALA cubosomes.…”
Section: G α-Lipoic Acidmentioning
confidence: 99%
“…If we can be mesmerized by the plethora of experimental models and assays for human skin pigmentation control, the sheer snowstorm of touted melanogenesis agents used in these assays can be enthralling if not bamboozling. These range from the exotically and dare I say hypnotically named botanicals 10–12 to the repackaging of some of our own human elixiric juices, for example taken from either our intra‐uterine lives (eg placental extracts 13,14 ) or from our increasingly appreciated super‐lipids 9,15 . My own laboratory has indulged a bit in this area too, 12 but journal editors are increasingly taking a jaundiced view of this area of skin and hair science, as it is just so difficult to separate the wheat from the chaff; the clinically relevant pigmentation modulator from the, well, sadly: “figment‐modulators”.…”
Section: Figurementioning
confidence: 99%
“…Though ALA is normally administered in oral or injection, it is rarely used topically because of its bad penetration. Kubota et.al, 2019 developed novel nanocapsule of ALA, named α-lipoactive (nLA), to improve skin permeability.In in vivo experiments, it was found that nLA is very effective for improving UV-induced pigmentation and epidermal thickening [151]. Sherif et.al, 2019 demonstrated application of topical 30% poloxamer gel loaded with ALA cubosomes.…”
Section: G α-Lipoic Acidmentioning
confidence: 99%